Multi-Source DEM Vertical Accuracy Evaluation of Taklimakan Desert Hinterland Based on ICESat-2 ATL08 and UAV Data - Mingyu Wang; Huoqing Li; Yongqiang Liu; Haojuan Li (Remote Sensing)
In earth science research, digital elevation models (DEMs) serve as essential tools for acquiring terrain information. However, existing research has primarily focused on geomorphic units like mountainous and forested regions, while research on extreme desert environments remains relatively scarce. This study systematically evaluates the vertical accuracy of six open-access DEMs in the hinterland of the Taklimakan Desert using ICESat-2 ATL08 data and unmanned aerial vehicle (UAV) data. Additionally, it examines the relationship between DEM errors and terrain characteristics, including slope, aspect, and terrain relief. The results reveal that the error distribution of different DEMs in the Taklimakan Desert hinterland follows a normal distribution pattern, but significant differences exist in both the magnitude and stability of the errors. Among the evaluated DEMs, Copernicus and AW3D30s exhibit superior performance, with moderate errors and high stability, making them suitable for high-precision terrain analysis. Further analysis indicates that terrain characteristics significantly influence DEM vertical accuracy in the TD hinterland. Specifically, increasing slope leads to a notable rise in errors across all assessed DEMs, with error fluctuations becoming more pronounced when the slope exceeds 15°. While slope aspect has a relatively minor impact on errors, certain DEMs exhibit error variations in the SE and NW directions. Similarly, increasing terrain relief results in greater errors. Moreover, research has demonstrated that ICESat-2 ATL08 data can effectively validate the vertical accuracy of DEMs in desert regions, offering valuable insights for DEM selection and correction in the hinterland of the Taklimakan Desert and similar arid environments.